Ob odnom balto-slavjanskom arhaizme: ‘3 x 9’Towards a Baltoslavic Archaism: ‘3 x 9’ - Žolobov, Oleg F. (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This article discusses the origin of the nonary scale of notation in the East Slavic and Latvian languages. In the Balto-Slavic part of monograph “Indo-European Numerals” B. Comrie mentions that the origin of the nonary scale of notation in these languages remains vague. Now it is possible to confirm that in its general features the Slavs’ nonary scale of notation has Indo-European roots. In the ancient chronological systems a 28-day month, consisting of four 7-day weeks, is based on the moon phase change, and a 27-day month, consisting of three 9-day weeks, corresponds to the period during which the Moon passes the Zodiac circle. This oposition has its justification in the modern astrophysical knowledge, according to which three varieties of the lunar month are distinguished. On the other hand, ‘9’ is a multiplication of numerus perfectus 3. It also means the full number of counting units on different levels of the decimal scale of notation.